Investigation of Formaldehyde Adsorption on Carbon Nanotubes by Density Functional Theory - Chen, Dazhi; Cao, Zhongqing; Yuan, Yong J. (Current Nanoscience, 2020)
Background: Formaldehyde (HCOH) is the most abundant airborne carbonyl indoor volatile organic compound (VOC), which is well-known to cause serious health effects such as respiratory system disease, immune system disorders, and central nervous system damage. Methods: The interaction between HCOH and intrinsic, congeners of Au, Ag, Cu-doped SWCNTs were investigated by density functional theory (DFT) to evaluate the detection of formaldehyde. Results: The results demonstrated that the less adsorption on the surface of intrinsic SWCNT, an HCOH molecule tended to be chemisorbed to the Au, Ag, and Cu atoms of doped SWCNT with larger binding energy of 0.4-0.8 eV and smaller binding distance of 1.9-2.3 Å. Furthermore, charge transfer and density of state studies indicated tha t the electronic properties changed evidently in the most stable HCOH-doped SWCNT systems, mainly at the region of -5.5 to -4.5 eV and Fermi level. Conclusion: More importantly, the adsorption of HCOH affected the electronic conductance of doped SWCNT. It is expected that the results obtained in this study could provide a useful theoretical guidance for the investigation of molecular films interface bonding and design of HCOH sensing devices.
Keywords: DFT